Transformation kinetics of selected steel grades after plastic deformation - R. Kawulok; I. Schindler; P. Kawulok; S. Rusz; P. Opěla; J. Kliber; Z. Solowski; K. M. Čmiel; P. Podolínský; M. Mališ; Z. Vašek; F. Vančura (Metalurgija, 2016)
The aim of this article was to assess the impact of previous plastic deformation on the kinetics of transformations of four selected steels. The research was conducted with use of the universal plastometer GLEEBLE 3800, when Continuous Cooling Transformation (CCT) and Deformation Continuous Cooling Transformation (DCCT) diagrams of selected steels were constructed on the basis of dilatometric tests. The research confirmed that the strain accelerates the particularly the transformations controlled by diffusion. Bainitic transformation was accelerated in three of the four steels. In the case of martensitic transformation the effect of the previous deformation was relatively small, but with clearly discernible trend.